An empirical research on effectiveness of knowledge management in achieving project success through Malaysian government agencies - Sabaghpour Azarian, Mahdieh; Yunus, Yunura Azura; Ahmad Dahlan, Abdul Rahman (IRPN Publishers, 2013)
As knowledge is being accepted as an inseparable imperative strategy of organization, organizations look at knowledge as a power which drives advantages to them. However, many organizations believe it is not about just the existence of knowledge but the organizational growth is being driven from the act of knowledge sharing. Through many established surveys, it is believed that in those organizations that their management and staff focus on practicing knowledge management and knowledge sharing will grow stronger and turn to be more competitive indeed rather than those organizations which lack of knowledge management practices. As modern economy takes knowledge as a point to achieve project success, utilization of information and data coupled with the harnessing of people’s skills and ideas as well as their commitments and motivations. Therefore, it is undeniable that today knowledge is an essential asset of every single organization and it has become more important than land, labor or capital in today’s economy. This paper investigates on the importance of knowledge management in generating of project success by analyzing whether or not government agencies in Malaysia, practice Knowledge Management. In this regard, a research has been conducted amongst fifteen Malaysian government agencies to find how effective project managers in Malaysian government agencies, integrate Knowledge Management criteria and factors in order to achieve project success and enhance citizen loyalty as well as gaining competitive advantage, the findings of this research worth to be considered.